(3GdeYdbGJ GdYTQs - (3dHjO Hf QHjYIs; (3WQag Hf GdYHO , WQaI Hf GdYHO Hf SajGf Hf SYO GdHcQj GdhGFdj, CHh YeQhs
(3ChdgG (B:s
(3bGd GeQD GdbjS Hf MLQ Hf GdMGQK GdcfOj(B: (3baG fHpc ef PcQi MHjH hefRd HSbW Gddhi Hjf GdONhd aMhed s
(3BNQgG (B:s
(3eHJhQ hBNQ GdehLhO efgG(B: (3fHFJ YeQkG ZjQ TGcQ fYeJj hGdcaQ eNHKg dfaS GdefYe s
(3cJHgG CcKQ ef fGSNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B225s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B70 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi edj (B- (3WgQGf (B(150(2)) s
Keywords: (3GdCOHs